ANALISIS DESKRIPTIF BUKU LE FRANÇAIS EN CONTEXTE TOURISME - Ima Damayanti Mustopa, - (2017)
This study aims to (1) describe the profile of Le Français en Contexte Tourisme's book, (2) describe the material that is contained in Le Français en Contexte Tourisme's Book, (3) assess the suitability of the material with the RPS of Français du Tourisme's courses of Department of French Language Education FPBS UPI and (4) Provide information on whether or not this book can be used as a reference for teaching material resources for Français du Tourisme course. This is due to the lack of reference material for the course of Français du Tourisme and considered that Le Français en Contexte Tourisme has never been used before by lecturers of the French Language Education Department FPBS UPI as a source of teaching material for Français du Tourisme's courses. Researchers using qualitative descriptive research method with the instruments form of (1) assessment sheet of Textbook Profile (by Lopez, 2001); (2) assessment sheet of Content Textbook (by Lopez, 2001) and (3) assessment Sheet of Textbook Conformity with RPS of Français du Tourisme (by Hanifah, 2014). From the result of the research, there are six main materials that is contained in this book, the materials are Les Métiers Du Tourisme, L'office De Tourisme, L'agence De Voyages, Les Transports, L'hébergement and L'événementiel. The results of this study indicate that the material contained in the book Le Français en Contexte Tourisme is in accordance with the RPS of Français du Tourisme's course, except for the absence of a single material, the Animation. But there are other materials that can be examined more deeply, such as material Premiers Contacts, Accueil and Les Transports. The materials may be used as reference material for the Français du Tourisme course French Language Education FPBS UPI.---- Penelitian ini bertujuan untuk: (1) mendeskripsikan profil buku Le Français en Contexte Tourisme; (2) mendeskripsikan materi-materi pembelajaran yang terdapat dalam Buku Le Français en Contexte Tourisme; (3) menganalisis kesesuaian materi yang terdapat dalam buku tersebut dengan RPS mata kuliah Français du Tourisme di Departemen Pendidikan Bahasa Perancis FPBS UPI; dan (4) memberikan informasi dapat atau tidaknya buku ini dijadikan sebagai referensi sumber bahan ajar untuk mata kuliah Français du Tourisme. Penelitian ini dilatarbelakangi oleh kurangnya referensi bahan ajar untuk mata kuliah Français du Tourisme dan buku Le Français en Contexte Tourisme belum pernah digunakan sebelumnya oleh dosen Departemen Pendidikan Bahasa Perancis FPBS UPI sebagai sumber bahan ajar untuk mata kuliah Français du Tourisme. Peneliti menggunakan metode penelitian deskriptif kualitatif dengan instrumen berupa (1) lembar Penilaian Profil Buku Teks (Lopez, 2001); (2) lembar Penilaian Isi Materi Buku Teks (Lopez, 2001) dan (3) lembar Penilaian Kesesuaian Buku Teks dengan RPS mata kuliah Français du Tourisme (Hanifah, 2014). Dari hasil penelitian yang dilakukan, terdapat enam materi utama di dalam buku ini, yakni materi Les métiers du tourisme, L'office de tourisme, L'agence de voyages, Les transports, L'hébergement dan L'événementiel. Hasil analisis menunjukkan bahwa sebagian besar materi yang terdapat dalam buku Le Français en Contexte Tourisme sesuai dengan RPS mata kuliah Français du Tourisme, namun tidak terdapat satu materi, yakni materi Animation. Sedangkan terdapat materi-materi lain yang dapat dipelajari lebih dalam, yaitu materi Premiers Contacts, Accueil dan Les Transports. Materi- materi tersebut dapat digunakan sebagai referensi bahan ajar untuk mata kuliah Français du Tourisme Pendidikan Bahasa Perancis FPBS UPI.